2016
DOI: 10.1089/thy.2015.0289
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Myeloid-Derived Suppressor Cells Predict Differentiated Thyroid Cancer Diagnosis and Extent

Abstract: Background: Establishing the preoperative diagnosis and long-term prognosis of differentiated thyroid cancer (DTC) remain challenging in some patients. Myeloid-derived suppressor cells (MDSC) are tumor-induced cells mediating immune tolerance that are detectable in the peripheral blood of cancer patients. The authors previously developed a novel clinical assay to detect the phenotypes of two human MDSC subsets in peripheral blood, and hypothesize that higher MDSC levels measured by this assay correlate positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 46 publications
1
49
1
1
Order By: Relevance
“…demonstrated that blood PMN‐MDSC correlate with the stage and persistence of DTC, and Suzuki et al . demonstrated increased levels of circulating MDSCs in patients with ATC …”
Section: Discussionmentioning
confidence: 97%
“…demonstrated that blood PMN‐MDSC correlate with the stage and persistence of DTC, and Suzuki et al . demonstrated increased levels of circulating MDSCs in patients with ATC …”
Section: Discussionmentioning
confidence: 97%
“…Several studies have indicated that as the tumor progresses there is an increase of MDSCs found in circulation. [21][22][23][24] On grouping patients with PCa by Gleason scores, we generally did not observe this with the only exception being between Gleason score 6 (G6) and Gleason score 7 (G7) for PMN-MDSCs ( Figure 2). More interestingly, there was a trend for M-MDSC levels to decrease with tumor progression, and unexpectedly, patients with BPH had a higher median level of M-MDSCs than patients with PCa albeit not statistically significant.…”
Section: Biomarker Assay Development: Immunophenotyping Differences Omentioning
confidence: 88%
“…Given that MDSC populations have been shown to be present in higher numbers in patients with cancer, we wanted to determine whether their gated counts could be used as an effective tool for detecting PCa. [21][22][23][24] The AUCs using the gated population percentage of live cells for eMDSCs, PMN-MDSCs, and M-MDSCs between HDM and patients with PCa were found to be 0.6791 (95% confidence interval [CI]: 0.6109-0.7472), 0.5178 (95% CI: 0.4457-0.5900), and 0.5473 (95% CI: 0.4745-0.6201), respectively ( Figure 1Q). The AUCs for all other measured populations based on gated percentage of live cells were determined, and CD14 + monocytes, CD16 − PMN, CD3 + lymphocytes, CD3 + T cells, CD4 + T cells, NKT cells, CD4 + NKT cells, CD8 + NKT cells, NK cells, and B cells were found to have AUCs greater than 0.6-all values greater than what was found for the PMN-MDSC and M-MDSC populations ( Supplementary Table S3).…”
Section: Biomarker Assay Development: Immunophenotyping Differences Omentioning
confidence: 99%
“…In thyroid cancers, the presence of MDSCs may even be a useful biomarker for distinguishing benign nodules from cancerous lesions. Specifically, there seems to be an association between higher preoperative levels of circulating MDSCs and thyroid cancers as compared to patients with benign nodules or other non-cancerous thyroid diseases (Suzuki et al 2013, Angell et al 2016. There also seems to be a correlation between numbers of circulating MDSCs and aggressive growth characteristics of differentiated thyroid cancers (Angell et al 2016).…”
Section: Myeloid Cellsmentioning
confidence: 99%
“…Specifically, there seems to be an association between higher preoperative levels of circulating MDSCs and thyroid cancers as compared to patients with benign nodules or other non-cancerous thyroid diseases (Suzuki et al 2013, Angell et al 2016. There also seems to be a correlation between numbers of circulating MDSCs and aggressive growth characteristics of differentiated thyroid cancers (Angell et al 2016). Prognoses could potentially be improved in thyroid cancer patients by either differentiating MDSCs into mature myeloid cells or depleting or functionally inhibiting them with various treatments, including some chemotherapeutics, nitric oxide inhibitors, tyrosine kinase inhibitors (e.g.…”
Section: Myeloid Cellsmentioning
confidence: 99%